Pembelajaran Berdiferensiasi Materi Ajar Dalam Kurikulum Merdeka Kajian Ilmu Pendidikan Islam - Salamudin, Ceceng; Kurniasih, Ani; Abdullah, Deba Muslim (STAI Al-Musaddadiyah Garut, 2025)
The concept of education is often used in a way that is not in accordance with the conditions of educators and students in Indonesia. Therefore, the Minister of Education, Culture, Research and Technology Nadiem Anwar Makarim implemented the Merdeka Curriculum as a solution to this problem. This independent curriculum is more flexible to support learning recovery caused by the COVID-19 pandemic and to catch up with Indonesia's education compared to other countries. This independent curriculum has something unique, namely differentiated learning, which consists of four elements, namely teaching materials, processes, products, and learning environments. The purpose of this research is to describe the concept of differentiated learning of teaching materials from the perspective of Islamic education science. Researchers used a qualitative approach with descriptive analysis method. The data collection technique used is literature research, and the data analysis technique uses content analysis techniques. The results showed that differentiated learning of teaching materials in the independent curriculum is a learning process that adapts teaching materials to meet the diverse needs of students in the classroom according to the interests, talents, and learning readiness of students. . In the study of Islamic Education, differentiated learning of teaching materials is in line with Islamic education, as contained in the Qur'an letter Al-Maidah verse 48 regarding anti-discrimination in education, as well as the content of letter At-Taubah verse 122 that requires a learner to explore a material. The alignment of differentiated learning of teaching materials with the concept of Islamic education is also seen in the suitability of educational components. Differentiated learning of teaching materials can create a more holistic educational environment, responsive to student diversity, and in accordance with Islamic values. Keywords: Independent curriculum, differentiated learning, teaching materials, Islamic Education.